Divine timelessness: A coherent but unfruitful doctrine? - Markus, Arjan (Sophia, 2004)
The author argues in this article that it is possible to have a consistent and coherent version of the doctrine of divine timelessness. Towards the objection that a timeless God cannot act it is defended that a timeless God can certainly act in the world and can love human people. In spite of the consistency and coherence of the doctrine of divine timelessness, however, the author has serious problems with the fruitfulness of this doctrine when it comes to essential practices of the Christian faith, such like seeking help from God, loving God, and prayer.